A review on contractual issues and aspects regarding Building Information Modelling (BIM) - Saraireh, Ibrahim Moh'd A. Q.; Ahmad Tarmizi, Haron (IJNIET, 2020)
BIM permits complete cooperation between project parties to imagine the future built in a simulated environment by determining any potential design and construction problems through the projects life cycle. Despite BIM is technically mature, until now its legal and contractual methods are not standardized. The construction industry in several countries is suffering from many challenges and insufficient productivity, so BIM is consider the future of the construction industry, it is the way to address these challenges. Although the BIM have huge benefits, there are various risks and problems impact in this technology, legal problems and contractual issues are minimizing and hindering the better adoption of BIM. So, the main aim of this study is to highlight an understanding about some concepts and issues, which lead to successful implementation of BIM, the major issues include: BIM definition, Benefits of BIM, understanding the construction contract, overview of contractual BIM adoption (theoretical frameworks) and Legal issues surrounding BIM adoption. The importance of this research is to determine the popular contractual issues and aspects that affect and impedes the applying of BIM in many countries, and to remedy them and reduce their disadvantageous effects in the construction projects.